Business Models for Sustainability From a System Dynamics Perspective. (March 2016) - Abdelkafi, Nizar; Täuscher, Karl
To achieve sustainability, a firm has to transform its entire business logic. A business model for sustainability (BMfS) aims at creating value for various stakeholders and the natural environment. This article advances the current understanding of the basic functioning of BMfS by applying a systems perspective. Our BMfS understanding incorporates the natural environment as an essential element, but does not deal with sustainability from a broad perspective. The core logic of a BMfS is built upon the creation of a reinforcing feedback loop between the created value to the customers, the value captured by the firm, and the value to the natural environment. Consequently, we develop a graphical model based on system dynamics notation. First, we conceptualize the basic feedback loops. Then, we propose partial models for the firm, natural environment, entrepreneur/manager, and customer, and then integrate these partial models within a systemic, multilevel model. Finally, we generate propositions that combine insights from the model and extant literature.